Violence and the Daniel tales in a children"s Bible - Nel, Marius (HTS teologiese studies, 2009)
Children enjoy the tales of Daniel and his three friends, whether told in Sunday school, day school, by parents or grandparents. These tales are cast essentially in violent terms. In this article a specific version of the tales in a children’s Bible is analysed to show in what way violence serves as the thread that holds the tales together and to suggest that this might imply that violence is condoned, be it violence committed by God for the sake of his children or by his children for their own sakes. Through ideology, criticism and deconstruction it is shown how a socially engaged reading of the text necessitates narrators of the Daniel tales to criticise violence embedded within the Biblical text, especially when these tales are narrated to children.